Dissociated time course recovery between rate of force development and peak torque after eccentric exercise - Molina, Renato [UNESP]; Denadai, Benedito S. [UNESP] (Wiley-Blackwell, 2012)
This study investigated the association between Isokinetic peak torque (PT) of quadriceps and the corresponding peak rate of force development (peak RFD) during the recovery of eccentric exercise. Twelve untrained men (aged 21.7 +/- 2.3 year) performed 100 maximal eccentric contractions for knee extensors (10 sets of 10 repetitions with a 2-min rest between each set) on isokinetic dynamometer. PT and peak RFD accessed by maximal isokinetic knee concentric contractions at 60 degrees s-1 were obtained before (baseline) and at 24 and 48 h after eccentric exercise. Indirect markers of muscle damage included delayed onset of muscle soreness (DOMS) and plasma creatine kinase (CK) activity. The eccentric exercise resulted in elevated DOMS and CK compared with baseline values. At 24 h, PT (-15.3%, P = 0.002) and peak RFD (-13.1%, P = 0.03) decreased significantly. At 48 h, PT (-7.9%, P = 0.002) was still decreased but peak RFD have returned to baseline values. Positive correlation was found between PT and peak RFD at baseline (r = 0.62, P = 0.02), 24 h (r = 0.99, P = 0.0001) and 48 h (r = 0.68, P = 0.01) after eccentric exercise. The magnitude of changes (%) in PT and peak RFD from baseline to 24 h (r = 0.68, P = 0.01) and from 24 to 48 h (r = 0.68, P = 0.01) were significantly correlated. It can be concluded that the muscle damage induced by the eccentric exercise affects differently the time course of PT and peak RFD recovery during isokinetic concentric contraction at 60 degrees s-1. During the recovery from exercise-induced muscle damage, PT and peak RFD are determined but not fully defined by shared putative physiological mechanisms.
Keywords: creatine kinase; delayed-onset muscle soreness; exercise-induced muscle damage; power; strength